2017
DOI: 10.1515/ev-2017-0004
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity and Health Outcomes

Abstract: Food insecurity is increasingly recognized as a major health crisis in the U.S. More than 42 million persons were food insecure in 2015, far higher than the levels preceding the 2007 Great Recession. Decades of research demonstrate that food insecurity diminishes individuals’ overall well-being. The recognition of food insecurity as a health crisis, however, stems from a more recent appreciation of the multiple negative health outcomes and, thus, higher health care costs, attributable to food insecurity. An ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
432
3
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 317 publications
(452 citation statements)
references
References 9 publications
15
432
3
2
Order By: Relevance
“…Many of the sociodemographic, clinical, and psychosocial predictors of food insecurity in KPCO members (Table , Supplemental Table S5) were consistent with findings of prior research in older adults. Food insecurity was more common in members of racial and ethnic minority groups, individuals with less education, and those who were unmarried or lived alone . Diabetes mellitus, depression, poorer self‐reported health, and limitations in activities of daily living were also more common in older KP members with food insecurity .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many of the sociodemographic, clinical, and psychosocial predictors of food insecurity in KPCO members (Table , Supplemental Table S5) were consistent with findings of prior research in older adults. Food insecurity was more common in members of racial and ethnic minority groups, individuals with less education, and those who were unmarried or lived alone . Diabetes mellitus, depression, poorer self‐reported health, and limitations in activities of daily living were also more common in older KP members with food insecurity .…”
Section: Discussionmentioning
confidence: 99%
“…Food insecurity, defined as lack of access to adequate food because of limited money or other resources, is an important social resource need for older Americans. In 2015, 12.7% of all U.S. households experienced food insecurity, including 8.3% of households with a member age 65 and older and 9.2% of older individuals living alone .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The HFSSM is a standard measure of food security in the US and is valid, reliable and widely used. 1,2,11 …”
Section: Methodsmentioning
confidence: 99%
“…4 Households described as having "low" and "very low" levels of food security are considered food insecure, whereas those with high or marginal levels of food security are considered food secure. 9,10 Longitudinal studies have suggested that food insecurity likely contributes to the development of chronic disease in some cases (through both nutritional and behavioral pathways), whereas chronic disease likely contributes to the development of food insecurity in other cases (by increasing health care expenditures and decreasing employability). Conversely, individuals in food-insecure households may experience such anxiety, as well as reductions in both the quality and quantity of food available.…”
Section: Food Insecurity and Adverse Health Outcomesmentioning
confidence: 99%